Investigation of mechanical properties of horn powder-filled epoxy composites - Kumar, Duraisamy (Strojniški vestnik, 2017)
Recent environmental concerns focus on the development of bio-composites, due to their low cost, and eco-friendly and bio-degradability characteristics. The aim of this work is to investigate the properties of particle-filled composites fabricated using bio-waste horn powder (HP) and epoxy resin. Composites were fabricated according to a Taguchi L 9 (3x3) orthogonal array. The HP particles and matrix were mixed in an appropriate ratio, compression-moulded and cured at room temperature to produce the specimens. Properties, such as ultimate tensile strength, tensile modulus, elongation percentage at break, flexural strength, flexural modulus, impact strength and microstructure of the specimens, were investigated. Scanning electron microscopy (SEM) micrographs of tensile tested specimens show good compatibility between HP particles and resin, when the HP volume is at 10 % and increases in agglomeration with increase in the HP volume percentage. Optimization of factors was done using grey relational analysis (GRA) and analysis of variance (ANOVA). The optimum factor levels were found to be the highest NaOH concentration (con.), A 3 (i.e., 0.3 N), the smallest HP size, B 1 (i.e., 125 microm) and the lowest HP volume percentage, C 1 (i.e., 10 %). The contribution of influencing factors in decreasing order were found to be, HP volume percentage with 90.87 %, HP size with 6.43 % and NaOH concentration with 0.78 %. From the R squared and R squared adjusted values of the properties, it is determined that most of the values are above 95 %, confirming a 95 % confidence level. Comparison between the optimum specimen and untreated HP specimens reveals that the optimum specimen has better properties. Hence, HP/epoxy composites can find application in various sectors
Keywords: epoksi smola; kompoziti z delci; mehanske lastnosti; optimizacija; roževina v prahu